Composite material for adsorbing VOCs as well as preparation method and application of composite material

By filling the foam metal frame with thermally conductive adsorbent materials and high-thermal silicone gel, the problems of poor thermal conductivity of adsorbent materials and the influence of binders are solved, and efficient VOCs adsorption and material strength improvement are achieved.

CN119258980APending Publication Date: 2025-01-07CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202310820036.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-05
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The poor thermal conductivity of existing adsorbent materials leads to accumulation of heat during adsorption, reducing adsorption efficiency, and traditional binders affect the pore structure of the material.

Method used

Using foam metal as the skeleton to fill the thermally conductive adsorbent materials, including porous materials and thermally conductive materials, and using high-thermal silicone gel as thermally conductive materials and binders, the thermally conductive materials are evenly filled through ultrasonic oscillation and settlement methods to avoid extrusion and molding. structural damage.

Benefits of technology

It improves adsorption efficiency, enhances the thermal conductivity and strength of the material, maintains the original pore structure, adapts to different bed filling requirements, and is suitable for VOCs treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119258980A_ABST
    Figure CN119258980A_ABST
Patent Text Reader

Abstract

The invention relates to the field of VOCs treatment, and discloses a composite material for adsorbing VOCs as well as a preparation method and application thereof. The composite material comprises foam metal and a heat-conducting adsorption material filled in a foam metal framework, the heat-conducting adsorption material comprises a porous material and a heat-conducting material. The composite material provided by the invention has the characteristic of good heat conduction effect, meanwhile, the shape and the size of the foam metal can be randomly adjusted according to the requirements of an adsorption bed layer, and the composite material can be used for adsorbing light hydrocarbons, such as small molecules such as ethane and propane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of VOCs treatment, and in particular to a composite material for absorbing VOCs, and a preparation method and application thereof. Background Art

[0002] Adsorption materials such as activated carbon, molecular sieves, and MOFs have relatively poor thermal conductivity. The heat generated during the VOCs adsorption determination process is slowly conducted, and the heat easily accumulates, causing the temperature of the entire adsorption bed to continue to rise. The adsorption capacity of the material decreases, seriously affecting the adsorption efficiency of the bed.

[0003] Adding thermal conductive materials such as graphene and carbon nanotubes during the granulation process of adsorbent materials such as activated carbon and MOFs can produce composite adsorbent materials with high thermal conductivity, which can transfer the heat generated by the adsorption bed to the environment and alleviate the temperature rise of the bed. However, this method requires the addition of additional binders, which will have a certain impact on the original pore structure of the adsorbent material. On the other hand, when the composite adsorbent material after molding is used to fill the adsorption tower, the filling rate of the bed is about 70%.

[0004] Patent application CN113713767A discloses a method for preparing activated carbon fibers modified with foamed aluminum. Multi-level porous foamed aluminum (micropore diameter is an average of 100 μm, mesopore diameter is 2 to 10 nm), activated carbon fiber powder with a particle size of less than 0.3 mm, and adhesive are put into a kneader and mixed evenly, and then extruded and molded by an extruder. This technical process is simple to operate and is widely used in the field of powder material molding. Although the addition of foamed metal can improve the high temperature resistance of activated carbon fibers, the pores of the foamed metal and the adsorbent material can easily collapse during the extrusion molding process, affecting the adsorption performance of the composite material.

[0005] Patent application CN113117647A discloses a foam metal supported adsorption material and its preparation method. A slurry of MOFs or COFs materials with a high BET specific surface area and a binder is dispersed in a foam metal with a porosity of 90% to 98% by vacuum filtration or pressure filtration to obtain a composite material. Under the action of the foam metal, the thermal conductivity of the material is enhanced, but the use of the binder causes a certain influence on the pore structure of the adsorption material.

[0006] Patent application CN110484213A discloses a shaped MOF-based composite phase change material and its preparation method. Using foam metal as the substrate for MOFs growth, the prepared MOFs mother liquid covers the foam metal surface to obtain a foam metal substrate, and then the substrate is placed in a MOFs reaction solution to allow MOFs to continue to grow on the substrate, and finally a composite material with the foam metal surface completely covered by MOFs is obtained, and finally the phase change material fills the foam gap to obtain a shaped MOF-based composite phase change material. The loading amount of MOFs in this material is very small, and it is difficult to apply it in VOCs adsorption occasions. Summary of the invention

[0007] The purpose of the present invention is to overcome the problem that the poor thermal conductivity of existing adsorption materials causes adsorption heat accumulation, thereby resulting in low material adsorption efficiency, and to provide a composite material for adsorbing VOCs and its preparation method and application.

[0008] In order to achieve the above-mentioned object, the present invention provides a composite material for adsorbing VOCs, wherein the composite material comprises a foam metal, and a thermally conductive adsorbent material filled in a foam metal skeleton;

[0009] The thermally conductive adsorption material comprises a porous material and a thermally conductive material.

[0010] Preferably, the porosity of the foam metal is 80-95%, the average pore size is 0.1-10 mm, and the compressive strength is not less than 250 kPa.

[0011] Preferably, the foam metal is selected from one or more of foam copper, foam aluminum and foam nickel.

[0012] Preferably, the thermally conductive material is selected from one or more of silicon carbide, graphite, graphene oxide, high thermal conductivity organic silicone grease and high thermal conductivity organic silicone gel.

[0013] Preferably, the thermally conductive material is a highly thermally conductive silicone gel.

[0014] Preferably, the porous material is selected from one or more of activated carbon, molecular sieve, silica gel and MOFs materials.

[0015] Preferably, the specific surface area of ​​the activated carbon is 400-2000m 2 / g, average pore diameter of 0.5-20nm, pore volume of 0.4-0.9cm 3 / g.

[0016] Preferably, the specific surface area of ​​the molecular sieve is 50-500m 2 / g, average pore diameter of 1-60nm, pore volume of 0.1-0.4cm 3 / g.

[0017] Preferably, the specific surface area of ​​the silica gel is 100-6000m 2 / g, average pore diameter of 1.5-50nm, pore volume of 0.1-0.6cm 3 / g.

[0018] Preferably, the specific surface area of ​​the MOFs material is 800-2500m 2 / g, average pore diameter of 0.5-5nm, pore volume of 0.4-1.1cm 3 / g.

[0019] The second aspect of the present invention provides a method for preparing the composite material for adsorbing VOCs, the preparation method comprising the following steps:

[0020] (1) mixing a thermally conductive material with an organic solvent to obtain a thermally conductive material mixture;

[0021] (2) mixing the porous material with the thermally conductive material mixture to obtain a slurry mixture;

[0022] (3) placing the foamed metal in the slurry mixture for ultrasonic vibration, followed by sedimentation to obtain a composite material precursor;

[0023] (4) air-drying and drying the composite material precursor.

[0024] Preferably, in step (1), the organic solvent is selected from one or more of methanol, ethanol, N,N-dimethylformamide, dichloromethane and 1,2-dichloroethane.

[0025] Preferably, in step (1), the organic solvent is ethanol.

[0026] Preferably, in step (1), the content of the thermally conductive material in the thermally conductive material mixture is 10-80 wt %.

[0027] Preferably, in step (2), the content of the porous material in the slurry mixture is 10-80 wt%.

[0028] Preferably, the weight ratio of the amount of the foam metal to the amount of the porous material is 0.15-0.2:1.

[0029] Preferably, in step (3), the ultrasonic oscillation time is 10-60 min.

[0030] Preferably, in step (3), the sedimentation time is 4-20 hours.

[0031] The third aspect of the present invention provides a use of the above-mentioned composite material for adsorbing VOCs in adsorbing VOCs.

[0032] The composite material for adsorbing VOCs of the present invention, wherein the dispersed heat-conducting material (such as high thermal conductivity organic silicone grease and high thermal conductivity organic silicone gel) has good thermal conductivity, can quickly transfer the heat generated by the adsorbent material in the process of adsorbing VOCs, avoid heat accumulation, and improve the bed adsorption efficiency. On the other hand, the heat-conducting material can act as a traditional binder, and after curing, it can increase the strength of the composite material, and avoid the influence of the original pore structure of the porous material caused by the use of traditional binders, thereby maintaining the adsorption performance of the adsorbent material. In addition, the foam metal with high shape plasticity as a skeleton can adapt to the filling requirements of different beds, and can further improve the thermal conductivity of the bed. At the same time, the deposition method can avoid the problem of structural damage caused by extrusion. The preparation process of this material is simple, the raw materials are easy to obtain, and it has the prospect of large-scale production and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 is a nitrogen adsorption isotherm graph of the composite material of Example 1;

[0034] Figure 2 is a breakthrough adsorption curve of ethane by the composite material of Example 1;

[0035] Figure 3 is a nitrogen adsorption isotherm graph of the composite material of Example 2;

[0036] Figure 4 is a breakthrough adsorption curve of ethane by the composite material of Example 2;

[0037] Figure 5 is a nitrogen adsorption isotherm graph of the composite material of Example 3;

[0038] Figure 6 is a breakthrough adsorption curve of ethane by the composite material of Example 3;

[0039] Figure 7 is a nitrogen adsorption isotherm graph of the composite material of Example 4;

[0040] Figure 8 is a breakthrough adsorption curve of ethane by the composite material of Example 4;

[0041] Fig. 9 is a nitrogen adsorption isotherm graph of the composite material of Example 5;

[0042] Fig.10 It is the breakthrough adsorption curve of ethane of the composite material of Example 5. DETAILED DESCRIPTION

[0043] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0044] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0045] In one aspect, the present invention provides a composite material for absorbing VOCs, the composite material comprising foam metal, and a thermally conductive adsorption material filled in the foam metal skeleton;

[0046] The thermally conductive adsorption material comprises a porous material and a thermally conductive material.

[0047] In the present invention, the thermally conductive material is filled in the gaps between the porous materials.

[0048] In the present invention, the porosity of the foam metal is 80-95%, the average pore size is 0.1-10 mm, and the compressive strength is not less than 250 kPa, and more preferably 250-750 kPa.

[0049] In a specific embodiment, the porosity of the foam metal can be 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94% or 95%, the average pore size can be 0.1mm, 1mm, 2mm, 3mm, 4mm, 5mm, 6mm, 7mm, 8mm, 9mm or 10mm, and the compressive strength can be 250kPa, 350kPa, 450kPa, 550kPa, 650kPa or 750kPa.

[0050] In the composite material of the present invention, preferably, the foam metal is selected from one or more of foam copper, foam aluminum and foam nickel.

[0051] In the composite material described in the present invention, in a preferred case, the thermally conductive material is selected from one or more of silicon carbide, graphite, graphene oxide, high thermal conductivity organic silicone grease and high thermal conductivity organic silicone gel.

[0052] Further preferably, the thermally conductive material is a high thermally conductive silicone gel. The high thermally conductive silicone gel is a special silicone rubber composed of liquid and solid, called "solid-liquid coexistence material". It has a network structure composed of polymer compounds and has unique properties. Before curing, it is generally divided into two components, A and B. It is obtained by the reaction of the vinyl or propylene group on the silicone resin matrix with the silicon hydrogen group on the cross-linking agent molecule under the catalytic action of a metal platinum compound.

[0053] In the composite material described in the present invention, in a preferred case, the porous material is selected from one or more of activated carbon, molecular sieve, silica gel and MOFs materials.

[0054] In a preferred embodiment, the specific surface area of ​​the activated carbon is 400-2000m 2 / g, average pore diameter of 0.5-20nm, pore volume of 0.4-0.9cm 3 / g.

[0055] In a specific embodiment, the specific surface area of ​​the activated carbon can be 400m 2 / g、600m 2 / g、800m 2 / g、1000m 2 / g、1200m 2 / g、1400m 2 / g、1600m 2 / g、1800m 2 / g or 2000m 2 / g, the average pore size can be 0.5nm, 1nm, 3nm, 5nm, 7nm, 10nm, 12nm, 15nm, 17nm or 20nm, and the pore volume can be 0.4cm 3 / g, 0.5cm 3 / g, 0.6cm 3 / g, 0.7cm 3 / g, 0.8cm 3 / g or 0.9cm 3 / g.

[0056] In a preferred embodiment, the molecular sieve has a specific surface area of ​​50-500 m 2 / g, average pore diameter of 1-60nm, pore volume of 0.1-0.4cm 3 / g.

[0057] In a specific embodiment, the specific surface area of ​​the molecular sieve can be 50m 2 / g、100m 2 / g, 150m 2 / g, 200m 2 / g, 250m 2 / g、300m 2 / g, 350m 2 / g, 400m 2 / g, 450m 2 / g or 500m 2 / g, the average pore size can be 1nm, 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm or 60nm, and the pore volume can be 0.1cm 3 / g, 0.2cm 3 / g, 0.3cm 3 / g or 0.4cm 3 / g.

[0058] In a preferred embodiment, the specific surface area of ​​the silica gel is 100-6000m 2 / g, average pore diameter of 1.5-50nm, pore volume of 0.1-0.6cm 3 / g.

[0059] In a specific embodiment, the specific surface area of ​​the silica gel can be 100m 2 / g、500m 2 / g、1000m 2 / g、1500m 2 / g, 2000m 2 / g, 2500m 2 / g、3000m 2 / g、3500m 2 / g, 4000m 2 / g, 4500m 2 / g、5000m 2 / g、5500m 2 / g or 6000m 2 / g, the average pore size can be 1.5nm, 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm or 50nm, and the pore volume can be 0.1cm 3 / g, 0.2cm 3 / g, 0.3cm 3 / g, 0.4cm 3 / g, 0.5cm 3 / g or 0.6cm 3 / g.

[0060] In a preferred embodiment, the specific surface area of ​​the MOFs material is 800-2500 m 2 / g, average pore diameter of 0.5-5nm, pore volume of 0.4-1.1cm 3 / g.

[0061] In a specific embodiment, the specific surface area of ​​the MOFs material can be 800 m 2 / g、1000m 2 / g、1200m 2 / g、1400m 2 / g、1600m 2 / g、1800m 2 / g, 2000m 2 / g, 2200m 2 / g, 2400m 2 / g or 2500m 2 / g, the average pore size can be 0.5nm, 1nm, 1.5nm, 2nm, 2.5nm, 3nm, 3.5nm, 4nm, 4.5nm or 5nm, and the pore volume can be 0.4cm 3 / g, 0.5cm 3 / g, 0.6cm 3 / g, 0.7cm 3 / g, 0.8cm 3 / g, 0.9cm 3 / g, 1cm 3 / g or 1.1cm 3 / g.

[0062] In the present invention, the pore volume refers to the total pore volume per unit mass of a porous material.

[0063] In the composite material of the present invention, the activated carbon, silica gel and molecular sieve may be commercially available products.

[0064] In a preferred embodiment, the MOFs material can be selected from one or more of HKUST-1, Al-MIL-53-TDC, UiO-66, Cr-MIL-101, MOF-5 and ZIF-8.

[0065] In the composite material of the present invention, the MOFs material can be obtained by commercial purchase or homemade. When the MOFs material is obtained by homemade, the preparation method of the MOFs material comprises the following steps:

[0066] (a) mixing a metal salt with water to obtain a metal salt solution;

[0067] (b) mixing an organic carboxylic acid ligand and an organic solvent to obtain an organic phase solution;

[0068] (c) mixing the metal salt solution with the organic phase solution, and then reacting them. After the reaction is completed, the solid and liquid are separated, and the obtained solid is washed and activated in sequence to obtain a MOFs material.

[0069] In step (a) of the present invention, the metal salt is a soluble metal salt, and the metal salt is selected from aluminum chloride, aluminum chloride hexahydrate, aluminum sulfate, aluminum acetate, ferric chloride, ferric chloride hexahydrate, ferric sulfate, ferric nitrate, ferric acetate, cupric chloride, cupric sulfate, cupric nitrate, cupric acetate, cupric acetate monohydrate, cupric sulfate pentahydrate, cupric nitrate trihydrate, chromium nitrate, chromium chloride, chromium sulfate, chromium acetate, chromium nitrate nonahydrate, chromium chloride hexahydrate, zirconium nitrate, zirconium chloride, zirconium sulfate, zirconium acetate, zirconium nitrate pentahydrate, zinc nitrate, zinc chloride, zinc sulfate, zinc acetate, nitric acid One or more of zinc hexahydrate, zinc sulfate heptahydrate, nickel nitrate, nickel chloride, nickel sulfate, nickel acetate, nickel sulfate hexahydrate, nickel nitrate hexahydrate, nickel chloride hexahydrate, cobalt nitrate, cobalt chloride, cobalt sulfate, cobalt acetate, cobalt chloride hexahydrate, cobalt nitrate hexahydrate, cobalt sulfate monohydrate, manganese nitrate, manganese chloride, manganese sulfate, manganese acetate, manganese sulfate monohydrate, manganese nitrate hexahydrate and manganese acetate dihydrate, and further one or more of aluminum chloride hexahydrate, copper acetate monohydrate, chromium nitrate nonahydrate, zinc nitrate hexahydrate and zirconium chloride.

[0070] In step (a) of the present invention, the content of metal salt in the metal salt solution is 3-60 g / L, specifically 3 g / L, 5 g / L, 10 g / L, 15 g / L, 20 g / L, 25 g / L, 30 g / L, 35 g / L, 40 g / L, 45 g / L, 50 g / L, 55 g / L or 60 g / L.

[0071] In step (b) of the present invention, the organic carboxylic acid ligand is selected from one or more of 2-methylterephthalic acid, 2-aminoterephthalic acid, 2-nitroterephthalic acid, 2-sulfonateterephthalic acid, 2,3-dihydroxyterephthalic acid, terephthalic acid, phthalic acid, trimesic acid, and 2,5-thiophene dicarboxylic acid, and is further selected from one or more of 2,5-thiophene dicarboxylic acid, trimesic acid, and terephthalic acid.

[0072] In step (b) of the present invention, the organic solvent is selected from one or more of methanol, ethanol, N,N-dimethylformamide (DMF), dichloromethane, and 1,2-dichloroethane.

[0073] In step (b) of the present invention, the content of organic carboxylic acid ligand in the organic phase solution is 10-160 g / L, specifically 10 g / L, 20 g / L, 30 g / L, 40 g / L, 50 g / L, 60 g / L, 70 g / L, 80 g / L, 90 g / L, 100 g / L, 110 g / L, 120 g / L, 130 g / L, 140 g / L, 150 g / L or 160 g / L.

[0074] In the present invention, the molar ratio of the metal salt to the organic carboxylic acid ligand is 1:0.5-2, specifically 1:0.5, 1:0.7, 1:0.8, 1:1, 1:1.2, 1:1.5, 1:1.7 or 1:2.

[0075] In step (c) of the present invention, the reaction conditions include: temperature of 40-110° C. and time of 4-13 h.

[0076] In a specific embodiment, in step (c), the reaction temperature can be 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C or 110°C, and the reaction time can be 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h or 13h.

[0077] In step (c) of the present invention, the obtained solid can be washed with an organic solvent to remove unreacted metal salts and organic ligands, etc. The organic solvent can be selected from one or more of methanol, ethanol, N,N-dimethylformamide, dichloromethane and 1,2-dichloroethane, preferably anhydrous ethanol is used for washing.

[0078] In step (c) of the present invention, there is no special requirement for the number of washings, and the unreacted metal salt and organic carboxylic acid ligand etc. can be removed.

[0079] In a preferred embodiment of the present invention, in step (c), the activation conditions include: temperature of 80-150° C., time of 6-14 h, and vacuum degree of 30-100 kPa.

[0080] In a specific embodiment, in step (c), the activation temperature can be 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C, the activation time can be 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h or 14h, and the activation vacuum degree can be 30kPa, 40kPa, 50kPa, 60kPa, 70kPa, 80kPa, 90kPa, 100kPa.

[0081] The second aspect of the present invention provides a method for preparing the composite material for adsorbing VOCs, the preparation method comprising the following steps:

[0082] (1) mixing a thermally conductive material with an organic solvent to obtain a thermally conductive material mixture;

[0083] (2) mixing the porous material with the thermally conductive material mixture to obtain a slurry mixture;

[0084] (3) placing the foamed metal in the slurry mixture for ultrasonic vibration, followed by sedimentation to obtain a composite material precursor;

[0085] (4) air-drying and drying the composite material precursor.

[0086] In the preparation method of the composite material for adsorbing VOCs described in the present invention, the thermal conductive material, the porous material and the organic solvent can also be directly mixed together. In a preferred case, in order to ensure that the thermal conductive material is dissolved evenly and better mixed with the porous material, the thermal conductive material is first fully mixed with the organic solution and then mixed with the porous material.

[0087] In the method for preparing a composite material for adsorbing VOCs described in the present invention, in step (1), the organic solvent is selected from one or more of methanol, ethanol, N,N-dimethylformamide, dichloromethane and 1,2-dichloroethane, and is more preferably ethanol.

[0088] In the method for preparing the composite material for adsorbing VOCs described in the present invention, preferably, in step (1), the thermally conductive material is selected from one or more of silicon carbide, graphite, graphene oxide, high thermal conductivity silicone grease and high thermal conductivity silicone gel.

[0089] Further preferably, in step (1), the thermally conductive material is a highly thermally conductive silicone gel.

[0090] In the method for preparing a composite material for adsorbing VOCs described in the present invention, in step (1), the content of the thermally conductive material in the thermally conductive material mixture is 10-80wt%, specifically 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt% or 80wt%.

[0091] In the method for preparing the composite material for adsorbing VOCs described in the present invention, preferably, in step (2), the porous material is selected from one or more of activated carbon, molecular sieves, silica gel and MOFs materials.

[0092] In a preferred embodiment of the present invention, in step (2), the specific surface area of ​​the activated carbon is 400-2000m 2 / g, average pore diameter of 0.5-20nm, pore volume of 0.4-0.9cm 3 / g.

[0093] In a specific embodiment of the present invention, in step (2), the specific surface area of ​​the activated carbon can be 400m 2 / g, 600m 2 / g、800m 2 / g、1000m 2 / g、1200m 2 / g、1400m 2 / g、1600m 2 / g、1800m 2 / g or 2000m 2 / g, the average pore size can be 0.5nm, 1nm, 3nm, 5nm, 7nm, 10nm, 12nm, 15nm, 17nm or 20nm, and the pore volume can be 0.4cm 3 / g, 0.5cm 3 / g, 0.6cm 3 / g, 0.7cm 3 / g, 0.8cm 3 / g or 0.9cm 3 / g.

[0094] In a preferred embodiment of the present invention, in step (2), the specific surface area of ​​the molecular sieve is 50-500m 2 / g, average pore diameter of 1-60nm, pore volume of 0.1-0.4cm 3 / g.

[0095] In a specific embodiment of the present invention, in step (2), the specific surface area of ​​the molecular sieve can be 50m 2 / g、100m 2 / g, 150m 2 / g, 200m 2 / g, 250m 2 / g、300m 2 / g, 350m 2 / g, 400m 2 / g, 450m 2 / g or 500m 2 / g, the average pore size can be 1nm, 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm or 60nm, and the pore volume can be 0.1cm 3 / g, 0.2cm 3 / g, 0.3cm 3 / g or 0.4cm 3 / g.

[0096] In a preferred embodiment of the present invention, in step (2), the specific surface area of ​​the silica gel is 100-6000m 2 / g, average pore diameter of 1.5-50nm, pore volume of 0.1-0.6cm 3 / g.

[0097] In a specific embodiment of the present invention, in step (2), the specific surface area of ​​the silica gel can be 100m 2 / g、500m 2 / g、1000m 2 / g、1500m 2 / g, 2000m 2 / g, 2500m 2 / g、3000m 2 / g、3500m 2 / g, 4000m 2 / g, 4500m 2 / g、5000m 2 / g、5500m 2 / g or 6000m 2 / g, the average pore size can be 1.5nm, 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm or 50nm, and the pore volume can be 0.1cm 3 / g, 0.2cm 3 / g, 0.3cm 3 / g, 0.4cm 3 / g, 0.5cm 3 / g or 0.6cm 3 / g.

[0098] In a preferred embodiment of the present invention, in step (2), the specific surface area of ​​the MOFs material is 800-2500 m 2 / g, average pore diameter of 0.5-5nm, pore volume of 0.4-1.1cm 3 / g.

[0099] In a specific embodiment of the present invention, in step (2), the specific surface area of ​​the MOFs material can be 800 m 2 / g、1000m 2 / g、1200m 2 / g、1400m 2 / g、1600m 2 / g、1800m 2 / g, 2000m 2 / g, 2200m 2 / g, 2400m 2 / g or 2500m 2 / g, the average pore size can be 0.5nm, 1nm, 1.5nm, 2nm, 2.5nm, 3nm, 3.5nm, 4nm, 4.5nm or 5nm, and the pore volume can be 0.4cm 3 / g, 0.5cm 3 / g, 0.6cm 3 / g, 0.7cm 3 / g, 0.8cm 3 / g, 0.9cm 3 / g, 1cm 3 / g or 1.1cm 3 / g.

[0100] In the method for preparing the composite material for adsorbing VOCs described in the present invention, the activated carbon, silica gel and molecular sieve can be commercially available products.

[0101] In a preferred embodiment, in step (2), the MOFs material can be selected from one or more of HKUST-1, Al-MIL-53-TDC, UiO-66, Cr-MIL-101, MOF-5 and ZIF-8.

[0102] In the preparation method of the composite material for adsorbing VOCs of the present invention, the MOFs material can be obtained by commercial purchase or homemade. When the MOFs material is obtained by homemade, the preparation method of the MOFs material comprises the following steps:

[0103] (a) mixing a metal salt with water to obtain a metal salt solution;

[0104] (b) mixing an organic carboxylic acid ligand and an organic solvent to obtain an organic phase solution;

[0105] (c) mixing the metal salt solution with the organic phase solution, and then reacting them. After the reaction is completed, the solid and liquid are separated, and the obtained solid is washed and activated in sequence to obtain a MOFs material.

[0106] In step (a) of the present invention, the metal salt is a soluble metal salt, and the metal salt is selected from aluminum chloride, aluminum chloride hexahydrate, aluminum sulfate, aluminum acetate, ferric chloride, ferric chloride hexahydrate, ferric sulfate, ferric nitrate, ferric acetate, cupric chloride, cupric sulfate, cupric nitrate, cupric acetate, cupric acetate monohydrate, cupric sulfate pentahydrate, cupric nitrate trihydrate, chromium nitrate, chromium chloride, chromium sulfate, chromium acetate, chromium nitrate nonahydrate, chromium chloride hexahydrate, zirconium nitrate, zirconium chloride, zirconium sulfate, zirconium acetate, zirconium nitrate pentahydrate, zinc nitrate, zinc chloride, zinc sulfate, zinc acetate, nitric acid One or more of zinc hexahydrate, zinc sulfate heptahydrate, nickel nitrate, nickel chloride, nickel sulfate, nickel acetate, nickel sulfate hexahydrate, nickel nitrate hexahydrate, nickel chloride hexahydrate, cobalt nitrate, cobalt chloride, cobalt sulfate, cobalt acetate, cobalt chloride hexahydrate, cobalt nitrate hexahydrate, cobalt sulfate monohydrate, manganese nitrate, manganese chloride, manganese sulfate, manganese acetate, manganese sulfate monohydrate, manganese nitrate hexahydrate and manganese acetate dihydrate, and further one or more of aluminum chloride hexahydrate, copper acetate monohydrate, chromium nitrate nonahydrate, zinc nitrate hexahydrate and zirconium chloride.

[0107] In step (a) of the present invention, the content of metal salt in the metal salt solution is 3-60 g / L, specifically 3 g / L, 5 g / L, 10 g / L, 15 g / L, 20 g / L, 25 g / L, 30 g / L, 35 g / L, 40 g / L, 45 g / L, 50 g / L, 55 g / L or 60 g / L.

[0108] In step (b) of the present invention, the organic carboxylic acid ligand is selected from one or more of 2-methylterephthalic acid, 2-aminoterephthalic acid, 2-nitroterephthalic acid, 2-sulfonateterephthalic acid, 2,3-dihydroxyterephthalic acid, terephthalic acid, phthalic acid, trimesic acid, and 2,5-thiophene dicarboxylic acid, and is further selected from one or more of 2,5-thiophene dicarboxylic acid, trimesic acid, and terephthalic acid.

[0109] In step (b) of the present invention, the organic solvent is selected from one or more of methanol, ethanol, N,N-dimethylformamide (DMF), dichloromethane, and 1,2-dichloroethane.

[0110] In step (b) of the present invention, the content of organic carboxylic acid ligand in the organic phase solution is 10-160 g / L, specifically 10 g / L, 20 g / L, 30 g / L, 40 g / L, 50 g / L, 60 g / L, 70 g / L, 80 g / L, 90 g / L, 100 g / L, 110 g / L, 120 g / L, 130 g / L, 140 g / L, 150 g / L or 160 g / L.

[0111] In the present invention, the molar ratio of the metal salt to the organic carboxylic acid ligand is 1:0.5-2, specifically 1:0.5, 1:0.7, 1:0.8, 1:1, 1:1.2, 1:1.5, 1:1.7 or 1:2.

[0112] In step (c) of the present invention, the reaction conditions include: temperature of 40-110° C. and time of 4-13 h.

[0113] In a specific embodiment, in step (c), the reaction temperature can be 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C or 110°C, and the reaction time can be 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h or 13h.

[0114] In step (c) of the present invention, the obtained solid can be washed with an organic solvent to remove unreacted metal salts and organic ligands, etc. The organic solvent can be selected from one or more of methanol, ethanol, N,N-dimethylformamide, dichloromethane and 1,2-dichloroethane, preferably anhydrous ethanol is used for washing.

[0115] In step (c) of the present invention, there is no special requirement for the number of washings, and the unreacted metal salt and organic carboxylic acid ligand etc. can be removed.

[0116] In a preferred embodiment of the present invention, in step (c), the activation conditions include: temperature of 80-150° C., time of 6-14 h, and vacuum degree of 30-100 kPa.

[0117] In a specific embodiment, in step (c), the activation temperature can be 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C, the activation time can be 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h or 14h, and the activation vacuum degree can be 30kPa, 40kPa, 50kPa, 60kPa, 70kPa, 80kPa, 90kPa, 100kPa.

[0118] In the method for preparing a composite material for adsorbing VOCs described in the present invention, preferably, in step (2), the content of the porous material in the slurry mixture is 10-80wt%, specifically 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt% or 80wt%.

[0119] In the method for preparing the composite material for adsorbing VOCs of the present invention, the porosity of the foam metal is 80-95%, the average pore size is 0.1-10 mm, and the compressive strength is not less than 250 kPa, and more preferably 250-750 kPa.

[0120] In a specific embodiment, the porosity of the foam metal can be 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94% or 95%, the average pore size can be 0.1mm, 1mm, 2mm, 3mm, 4mm, 5mm, 6mm, 7mm, 8mm, 9mm or 10mm, and the compressive strength can be 250kPa, 350kPa, 450kPa, 550kPa, 650kPa or 750kPa.

[0121] In the method for preparing the composite material for adsorbing VOCs of the present invention, preferably, the foam metal is selected from one or more of foam copper, foam aluminum and foam nickel.

[0122] In the preparation method of the composite material for adsorbing VOCs described in the present invention, the foam metal needs to be washed to remove oil and dust on the surface of the foam metal, and then placed in a slurry mixture for ultrasonic vibration after drying.

[0123] In the preparation method of the composite material for adsorbing VOCs of the present invention, the foam metal is washed with acetic acid, distilled water and anhydrous ethanol in sequence.

[0124] In the method for preparing the composite material for adsorbing VOCs described in the present invention, the weight ratio of the amount of the foam metal to the amount of the porous material is 0.15-0.2:1, specifically 0.15:1, 0.16:1, 0.17:1, 0.18:1, 0.19:1 or 0.2:1.

[0125] In the method for preparing a composite material for adsorbing VOCs described in the present invention, preferably, in step (3), the time of the ultrasonic oscillation is 10-60 min, specifically 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min or 60 min.

[0126] In the preparation method described in the present invention, in step (3), the sedimentation time is 4-20h, specifically 4h, 5h, 6h, 7h, 8h, 4h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h or 20h.

[0127] In step (3) of the present invention, the ultrasonic oscillation and sedimentation operations are both carried out at room temperature.

[0128] In the preparation method described in the present invention, in step (4), under preferred circumstances, the air-drying time is 20-50 h, specifically 20 h, 22 h, 24 h, 26 h, 28 h, 30 h, 32 h, 34 h, 36 h, 38 h, 40 h, 42 h, 44 h, 46 h, 48 h or 50 h.

[0129] In the preparation method of the present invention, in step (4), under preferred circumstances, the drying conditions include: a temperature of 40-80°C and a time of 1-8h. Specifically, the drying temperature may be 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C, and the drying time may be 1h, 2h, 3h, 4h, 5h, 6h, 7h or 8h.

[0130] The composite material prepared by the preparation method of the present invention, wherein the weight ratio of the foam metal, the thermal conductive material and the porous material is 0.1-0.2:0.05-0.2:1, specifically, the weight ratio of the foam metal to the porous material can be 0.1:1, 0.12:1, 0.15:1, 0.17:1 or 0.2:1, and the weight ratio of the thermal conductive material to the porous material can be 0.05:1, 0.07:1, 0.09:1, 0.1:1, 0.12:1, 0.15:1, 0.17:1, 0.19:1 or 0.2:1.

[0131] The third aspect of the present invention provides a use of the above-mentioned composite material for adsorbing VOCs in adsorbing VOCs.

[0132] Compared with the prior art, the present invention has the following advantages:

[0133] 1. The composite material for adsorbing VOCs prepared by the present invention uses foam metal as a skeleton, and its shape has extremely high plasticity, which can adapt to the filling requirements of different bed layers, greatly improving the filling efficiency of the adsorption material.

[0134] 2. The high thermal conductivity silicone gel in the composite material provided by the present invention is used as a thermal conductive material, and together with the foam metal, it strengthens the adsorption heat conduction during the adsorption process and improves the adsorption efficiency of the material. In addition, it can also be used as a binder to enhance the strength of the porous material molding, avoid the influence of the original pore structure of the porous material due to the use of traditional binders, and maintain the adsorption performance of the adsorption material.

[0135] 3. The composite material provided by the present invention adopts the method of ultrasonic vibration plus static sedimentation, and the thermal conductive adsorption material is evenly filled in the foam metal, and the formed material is not easy to fall off.

[0136] The composite material provided by the present invention has the characteristics of good thermal conductivity. At the same time, the shape and size of the foam metal can be adjusted at will according to the needs of the adsorption bed. It can be used in the field of VOCs treatment, especially for adsorbing light hydrocarbons, such as ethane, propane and other small molecules.

[0137] The present invention will be described in detail below through examples, but the scope of protection of the present invention is not limited thereto.

[0138] In the following examples, copper acetate monohydrate and aluminum chloride hexahydrate are products of Shanghai Aladdin Biochemical Technology Co., Ltd., zirconium chloride, trimesic acid, 2,5-thiophene dicarboxylic acid, and terephthalic acid are products of Shanghai MacLean Biochemical Technology Co., Ltd., anhydrous ethanol, DMF, and acetic acid are products of China National Pharmaceutical Group Co., Ltd., foamed copper (porosity of 92%, average pore size of 1 mm, compressive strength of 300 kPa) and foamed aluminum (porosity of 92%, average pore size of 1 mm, compressive strength of 280 kPa) are products of Guangshengjia New Materials Co., Ltd., activated carbon AC-1 (specific surface area of ​​1131 m 2 / g, average pore diameter of 1.96nm, pore volume of 0.74cm 3 / g), activated carbon AC-2 (specific surface area 791m 2 / g, average pore diameter of 3.05nm, pore volume of 0.45cm 3 / g) is the product of Shanghai Lekang Activated Carbon Co., Ltd., high thermal conductivity silicone grease and high thermal conductivity silicone gel are the products of Shenzhen Nuofeng Electronic Technology Co., Ltd., silicon carbide (particle size 400 mesh) is the product of Shanghai Aladdin Biochemical Technology Co., Ltd., and graphite powder (particle size 800 mesh) is the product of Shanghai Haohong Biomedicine Technology Co., Ltd.

[0139] The room temperature below refers to 25℃.

[0140] Example 1

[0141] (1) Weigh 2.8 g of a metal salt (copper acetate monohydrate) and add it to a beaker containing water. Perform ultrasonic mixing at room temperature to obtain a metal salt solution (the content of the metal salt in the metal salt solution is 46 g / L);

[0142] (2) Weigh 3.8 g of an organic carboxylic acid ligand (trimellitic acid) and add it to a beaker containing an organic solvent (anhydrous ethanol), and perform ultrasonication at room temperature to mix the mixture evenly to obtain an organic phase solution (the content of the organic carboxylic acid ligand in the organic phase solution is 82 g / L);

[0143] (3) The metal salt solution and the organic phase solution were added to a reaction bottle and mixed evenly (the molar ratio of the metal salt to the organic carboxylic acid ligand was 1:1.3), placed in an oil bath, reacted at 60°C for 4 hours, and a suspension was obtained after the reaction was completed. After the suspension cooled to room temperature, it was centrifuged and the obtained solid was washed twice with anhydrous ethanol. The washed solid was then placed in a vacuum oven and activated at 90°C and a vacuum degree of 60 kPa for 8 hours to obtain a MOFs material (HKUST-1, with a specific surface area of ​​1657 m2 measured by BET). 2 / g, average pore diameter of 0.61nm, pore volume of 0.82cm 3 / g).

[0144] (4) dissolving 0.5 g of a thermally conductive material (high thermally conductive silicone gel) in an organic solvent (anhydrous ethanol) to obtain a thermally conductive material mixture (the content of the thermally conductive material in the thermally conductive material mixture is 23.8 wt %);

[0145] (5) mixing 3 g of the porous material (HKUST-1) with the thermal conductive material mixture to obtain a slurry mixture (the content of the porous material in the slurry mixture is 58.8 wt %);

[0146] (6) washing a piece of foamed metal (foamed copper) of suitable size with acetic acid, distilled water and anhydrous ethanol in sequence, and placing it in a mold of suitable size after drying, and pouring the slurry mixture obtained in step (5) into it (the weight ratio of the amount of foamed metal to the amount of porous material in step (5) is 0.15:1), and completely immersing the foamed metal in the slurry mixture by ultrasonic vibration for 15 minutes, and then standing and settling for 15 hours (the ultrasonic vibration and standing and settling operations are both performed at room temperature), to obtain a composite material precursor;

[0147] (7) The composite material precursor was taken out and placed in a ventilated place for air drying for 25 hours, and then placed in a 60° C. oven for drying for 4 hours to obtain composite material A1.

[0148] Example 2

[0149] (1) Weigh 3.1 g of a metal salt (aluminum chloride hexahydrate) and add it to a beaker containing water. Perform ultrasonic mixing at room temperature to obtain a metal salt solution (the content of the metal salt in the metal salt solution is 20 g / L);

[0150] (2) Weighing 3.5 g of an organic carboxylic acid ligand (2,5-thiophenedicarboxylic acid (TDC)) into a beaker containing an organic solvent (DMF), and performing ultrasonication at room temperature to mix the mixture evenly to obtain an organic phase solution (the content of the organic carboxylic acid ligand in the organic phase solution is 60 g / L);

[0151] (3) The metal salt solution and the organic phase solution were added to a reaction bottle and mixed evenly (the molar ratio of the metal salt to the organic carboxylic acid ligand was 1:1.58), placed in an oil bath, and reacted at 100°C for 8 hours. After the reaction, a suspension was obtained. After the suspension cooled to room temperature, it was centrifuged and the obtained solid was washed twice with anhydrous ethanol. The washed solid was then placed in a vacuum oven and activated at 110°C and a vacuum degree of 60 kPa for 6 hours to obtain a MOFs material (Al-MIL-53-TDC, with a specific surface area of ​​1320 m2 measured by BET). 2 / g, average pore diameter of 0.65nm, pore volume of 0.58cm 3 / g).

[0152] (4) dissolving 0.5 g of a thermally conductive material (high thermally conductive silicone gel) in an organic solvent (anhydrous ethanol) to obtain a thermally conductive material mixture (the content of the thermally conductive material in the thermally conductive material mixture is 23.8 wt %);

[0153] (5) 3 g of porous material (Al-MIL-53-TDC) was mixed with the thermal conductive material mixture to obtain a slurry mixture (the content of the porous material in the slurry mixture was 58.8 wt %);

[0154] (6) washing a piece of foamed metal (foamed aluminum) of suitable size with acetic acid, distilled water and anhydrous ethanol in sequence, and placing it in a mold of suitable size after drying, and pouring the slurry mixture obtained in step (5) into it (the weight ratio of the amount of foamed metal to the amount of porous material in step (5) is 0.16:1), and completely immersing the foamed metal in the slurry mixture by ultrasonic vibration for 20 minutes, and then allowing it to settle for 20 hours (the ultrasonic vibration and the settling operation are both performed at room temperature), to obtain a composite material precursor;

[0155] (7) The composite material precursor was taken out and placed in a ventilated place for air drying for 25 hours, and then placed in a 70° C. oven for drying for 4 hours to obtain composite material A2.

[0156] Example 3

[0157] (1) Weigh 1.2 g of a metal salt (zirconium chloride) and add it to a beaker containing water, and perform ultrasonic mixing at room temperature to obtain a metal salt solution (the content of the metal salt in the metal salt solution is 45 g / L);

[0158] (2) Weighing 1.1 g of an organic carboxylic acid ligand (terephthalic acid) was added to a beaker containing an organic solvent (DMF), and ultrasonically mixed at room temperature to obtain an organic phase solution (the content of the organic carboxylic acid ligand in the organic phase solution was 110 g / L);

[0159] (3) The metal salt solution and the organic phase solution are added to the reaction kettle and mixed evenly (the molar ratio of the metal salt to the organic carboxylic acid ligand is 1:1.29), placed in an oven, reacted at 110° C. for 10 h, and a suspension is obtained after the reaction is completed. After the suspension cools to room temperature, it is centrifuged and the obtained solid is washed twice with anhydrous ethanol. The washed solid is then placed in a vacuum oven and activated at 120° C. and a vacuum degree of 70 kPa for 8 h to obtain a MOFs material (UiO-66, with a specific surface area of ​​1106 m 2 / g, average pore diameter of 0.66nm, pore volume of 0.53cm 3 / g).

[0160] (4) dissolving 0.5 g of a thermally conductive material (high thermally conductive silicone gel) in an organic solvent (anhydrous ethanol) to obtain a thermally conductive material mixture (the content of the thermally conductive material in the thermally conductive material mixture is 23.8 wt %);

[0161] (5) mixing 3 g of a porous material (UiO-66) with the thermal conductive material mixture to obtain a slurry mixture (the content of the porous material in the slurry mixture is 58.8 wt %);

[0162] (6) washing a piece of foamed metal (foamed copper) of suitable size with acetic acid, distilled water and anhydrous ethanol in sequence, and placing it in a mold of suitable size after drying, and pouring the slurry mixture obtained in step (5) into it (the weight ratio of the amount of foamed metal to the amount of porous material in step (5) is 0.18:1), and completely immersing the foamed metal in the slurry mixture by ultrasonic vibration for 15 minutes, and then standing and settling for 15 hours (the ultrasonic vibration and standing and settling operations are both performed at room temperature) to obtain a composite material precursor;

[0163] (7) The composite material precursor was taken out and placed in a ventilated place for air drying for 25 hours, and then placed in a 60° C. oven for drying for 4 hours to obtain composite material A3.

[0164] Example 4

[0165] (1) dissolving 0.5 g of a thermally conductive material (high thermally conductive silicone gel) in an organic solvent (anhydrous ethanol) to obtain a thermally conductive material mixture (the content of the thermally conductive material in the thermally conductive material mixture is 17.2 wt %);

[0166] (2) 3.5 g of porous material (activated carbon AC-1, BET specific surface area of ​​1131 m 2 / g, average pore diameter of 1.96nm, pore volume of 0.74cm 3 / g) and the thermal conductive material mixture to obtain a slurry mixture (the content of the porous material in the slurry mixture is 54.7wt%);

[0167] (3) washing a piece of foamed metal (foamed copper) of suitable size with acetic acid, distilled water and anhydrous ethanol in sequence, placing it in a mold of suitable size after drying, pouring the slurry mixture obtained in step (2) into it (the weight ratio of the amount of foamed metal to the amount of porous material in step (2) is 0.2:1), completely immersing the foamed metal in the slurry mixture by ultrasonic vibration for 15 minutes, and then allowing it to settle for 15 hours (the ultrasonic vibration and the settling operation are both performed at room temperature), to obtain a composite material precursor;

[0168] (4) The composite material precursor was taken out and placed in a ventilated place for air drying for 25 hours, and then placed in a 60° C. oven for drying for 4 hours to obtain composite material A4.

[0169] Example 5

[0170] (1) dissolving 0.6 g of a thermally conductive material (high thermally conductive silicone gel) in an organic solvent (anhydrous ethanol) to obtain a thermally conductive material mixture (the content of the thermally conductive material in the thermally conductive material mixture is 30 wt %);

[0171] (2) 3 g of porous material (activated carbon AC-2, BET measured specific surface area of ​​791 m 2 / g, average pore diameter of 3.05nm, pore volume of 0.45cm 3 / g) and the thermally conductive material mixture to obtain a slurry mixture (the content of the porous material in the slurry mixture is 60wt%);

[0172] (3) washing a piece of foamed metal (foamed copper) of suitable size with acetic acid, distilled water and anhydrous ethanol in sequence, placing it in a mold of suitable size after drying, pouring the slurry mixture obtained in step (2) into it (the weight ratio of the amount of foamed metal to the amount of porous material in step (2) is 0.2:1), completely immersing the foamed metal in the slurry mixture by ultrasonic vibration for 15 minutes, and then allowing it to settle for 15 hours (the ultrasonic vibration and the settling operation are both performed at room temperature), to obtain a composite material precursor;

[0173] (4) The composite material precursor was taken out and placed in a ventilated place for air drying for 25 hours, and then placed in a 60° C. oven for drying for 4 hours to obtain composite material A5.

[0174] Example 6

[0175] (1) dissolving 0.5 g of a thermally conductive material (high thermally conductive silicone gel) in an organic solvent (anhydrous ethanol) to obtain a thermally conductive material mixture (the content of the thermally conductive material in the thermally conductive material mixture is 23.8 wt %);

[0176] (2) mixing 3 g of porous material (1.5 g of activated carbon AC-1 and 1.5 g of the MOFs material HKUST-1 prepared in Example 1) with the thermal conductive material mixture to obtain a slurry mixture (the content of the porous material in the slurry mixture is 58.8 wt %);

[0177] (3) washing a piece of foamed metal (foamed copper) of suitable size with acetic acid, distilled water and anhydrous ethanol in sequence, placing it in a mold of suitable size after drying, pouring the slurry mixture obtained in step (2) into it (the weight ratio of the amount of foamed metal to the amount of porous material in step (2) is 0.15:1), completely immersing the foamed metal in the slurry mixture by ultrasonic vibration for 15 minutes, and then allowing it to settle for 15 hours (the ultrasonic vibration and the settling operation are both performed at room temperature), to obtain a composite material precursor;

[0178] (4) The composite material precursor was taken out and placed in a ventilated place for air drying for 25 hours, and then placed in a 60° C. oven for drying for 4 hours to obtain composite material A6.

[0179] Example 7

[0180] (1) dissolving 0.5 g of a thermally conductive material (high thermally conductive silicone gel) in an organic solvent (anhydrous ethanol) to obtain a thermally conductive material mixture (the content of the thermally conductive material in the thermally conductive material mixture is 23.8 wt %);

[0181] (2) 3 g of porous material (1.5 g of activated carbon AC-2 and 1.5 g of the MOFs material Al-MIL-53-TDC prepared in Example 2) was mixed with the thermal conductive material mixture to obtain a slurry mixture (the content of the porous material in the slurry mixture was 58.8 wt %);

[0182] (3) washing a piece of foam metal (foam aluminum) of suitable size with acetic acid, distilled water and anhydrous ethanol in sequence, placing it in a mold of suitable size after drying, pouring the slurry mixture obtained in step (2) (the weight ratio of the amount of foam metal to the amount of porous material in step (5) is 0.15:1), completely immersing the foam metal in the slurry mixture by ultrasonic vibration for 20 minutes, and then allowing it to settle for 20 hours (the ultrasonic vibration and the settling operation are both performed at room temperature), to obtain a composite material precursor;

[0183] (4) The composite material precursor was taken out and placed in a ventilated place for air drying for 25 hours, and then placed in a 70° C. oven for drying for 4 hours to obtain a composite material A7.

[0184] Example 8

[0185] (1) dissolving 0.5 g of a thermally conductive material (high thermally conductive silicone gel) in an organic solvent (anhydrous ethanol) to obtain a thermally conductive material mixture (the content of the thermally conductive material in the thermally conductive material mixture is 23.8 wt %);

[0186] (2) 3 g of porous material (1 g of activated carbon AC-1, 0.5 g of activated carbon AC-2 and 1.5 g of the MOFs material UiO-66 prepared in Example 3) was mixed with the thermal conductive material mixture to obtain a slurry mixture (the content of the porous material in the slurry mixture was 58.8 wt %);

[0187] (3) washing a piece of foamed metal (foamed copper) of suitable size with acetic acid, distilled water and anhydrous ethanol in sequence, placing it in a mold of suitable size after drying, pouring the slurry mixture obtained in step (2) into it (the weight ratio of the amount of foamed metal to the amount of porous material in step (2) is 0.15:1), completely immersing the foamed metal in the slurry mixture by ultrasonic vibration for 20 minutes, and then allowing it to settle for 20 hours (the ultrasonic vibration and the settling operation are both performed at room temperature), to obtain a composite material precursor;

[0188] (4) The composite material precursor was taken out and placed in a ventilated place for air drying for 25 hours, and then placed in a 70° C. oven for drying for 4 hours to obtain a composite material A8.

[0189] Example 9

[0190] The method of Example 1 was followed, except that the thermally conductive material used was silicon carbide powder, to obtain a composite material A9.

[0191] Example 10

[0192] The method of Example 1 was followed, except that the thermally conductive material used was graphite powder, to obtain a composite material A10.

[0193] Embodiment 11

[0194] The method of Example 4 was followed, except that the thermally conductive material used was graphite powder, to obtain a composite material A11.

[0195] Comparative Example 1

[0196] (1) dissolving 0.05 g of a binder (methyl cellulose) in an organic solvent (anhydrous ethanol) to obtain a binder solution (the content of the binder in the binder solution is 3 wt %);

[0197] (2) mixing 3 g of a porous material (the MOFs material HKUST-1 prepared in Example 1) with the binder solution to obtain a slurry mixture (the content of the porous material in the slurry mixture is 64.5 wt %);

[0198] (3) washing a piece of foamed metal (foamed copper) of suitable size with acetic acid, distilled water and anhydrous ethanol in sequence, placing it in a mold of suitable size after drying, pouring the slurry mixture obtained in step (2) into it (the weight ratio of the amount of foamed metal to the amount of porous material in step (2) is 0.2:1), completely immersing the foamed metal in the slurry mixture by ultrasonic vibration for 15 minutes, and then allowing it to settle for 15 hours (the ultrasonic vibration and the settling operation are both performed at room temperature), to obtain a composite material precursor;

[0199] (4) The composite material precursor was taken out and placed in a ventilated place for air drying for 25 hours, and then placed in a 60° C. oven for drying for 4 hours to obtain a composite material D1.

[0200] Comparative Example 2

[0201] The method of Comparative Example 1 was followed, except that the porous material used was activated carbon AC-1, to obtain a composite material D2.

[0202] Test Example 1

[0203] The specific surface area, total pore volume, maximum temperature of the adsorption process, ethane adsorption amount and thermal conductivity of A1-A11 and D1-D2 were measured respectively.

[0204] Thermal conductivity measurement: The surface of the dried sample to be tested is flattened, and graphite coating is evenly sprayed on both sides. The thermal conductivity of the sample is measured by a laser thermal conductivity meter.

[0205] Specific surface area and total pore volume determination: The specific surface area and total pore volume of the sample were determined using a BSD-PM2 specific surface analyzer from Beijing Best Instrument Technology Co., Ltd. The operating steps were as follows: about 100 mg of powder sample was weighed, vacuum degassed at 150°C for 12 h, and then tested at liquid nitrogen temperature (-196°C) using nitrogen as a probe molecule to obtain the corresponding data;

[0206] The total pore volume of the material was calculated based on the measured nitrogen adsorption isotherm, and the BET specific surface area of ​​the material was calculated using the BET multi-point method.

[0207] Determination of ethane adsorption: The multi-component adsorption breakthrough curve analyzer (BSD-MAB) of Best Instrument Technology (Beijing) Co., Ltd. was used to measure the breakthrough curve of ethane gas for each sample, and the adsorption amount of ethane was calculated. The highest temperature during the adsorption process was measured by the temperature sensor on the analyzer.

[0208] The specific operation process for determining the breakthrough curve of ethane gas is as follows: first, weigh about 150g of sample and load it into the penetration column, purge it with helium at a flow rate of 300mL / min for 2h to remove impurity gases on the surface of the sample, and then test the ethane breakthrough adsorption curve (gas flow rate is 1800mL / min, ethane concentration is 10%VOL, test temperature and pressure are 25℃ and 5bar respectively), and calculate the adsorption amount.

[0209] The adsorption amount of each component was calculated by the following formula:

[0210]

[0211] Note: This calculation formula takes into account the concentration change caused by the real-time change of the outlet flow rate due to adsorption, which improves the accuracy of calculating the adsorption amount by concentration integral.

[0212] Q n吸附 : The amount of adsorbent adsorbed on adsorbate n (unit: mL)

[0213] Q n入总 : The total flow rate of adsorbate n flowing into the column within the time ΔT (unit: mL)

[0214] Q n出总 : The total flow rate of adsorbate n flowing out of the column within the time ΔT (unit: mL)

[0215] q 总入 : Total gas flow rate through the column inlet (unit: mL / min)

[0216] q 载气 : Carrier gas flow rate (unit: mL / min)

[0217] C n0 : The percentage concentration of adsorbate n at the entrance of the penetration column (%)

[0218] C nt : The percentage concentration of adsorbate n at a certain moment at the outlet of the penetration column (%)

[0219] ΔT: total time from the start to the end of adsorption (unit: min) for the adsorption amount of each component.

[0220] The results are shown in Table 1 and Figure 1-10 As shown ( Figure 1 is the nitrogen adsorption isotherm of A1. Figure 2 This is the breakthrough adsorption curve of A1 for ethane. Figure 3 is the nitrogen adsorption isotherm of A2. Figure 4 is the breakthrough adsorption curve of A2 for ethane, Figure 5 is the nitrogen adsorption isotherm of A3. Figure 6This is the breakthrough adsorption curve of A3 for ethane. Figure 7 is the nitrogen adsorption isotherm of A4. Figure 8 This is the breakthrough adsorption curve of A4 for ethane. Fig. 9 is the nitrogen adsorption isotherm of A5. Fig.10 (a) is the breakthrough adsorption curve of A5 for ethane.

[0221] Table 1

[0222]

[0223] From the above results, it can be seen from Examples 1-8 that this method is applicable to different types of MOFs materials. Composite materials A1-A8 have high thermal conductivity and can quickly transfer adsorption heat during the adsorption process to avoid the generation of high-temperature hot spots. During the penetration adsorption process, due to the presence of the thermal conductive material, the temperature rise of the embodiment is significantly lower than that of the comparative example, and the ethane adsorption capacity is higher than that of the comparative example.

[0224] A9-A11 show that the thermal conductivity and adsorption capacity of the composite materials prepared from graphite and silicon carbide are slightly worse than those of the high thermal conductivity silicone gel.

[0225] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A composite material for adsorbing VOCs, characterized in that: The composite material includes foam metal and a heat-conducting adsorption material filled in the foam metal skeleton; The thermally conductive adsorption material comprises a porous material and a thermally conductive material.

2. The composite material according to claim 1, characterized in that The porosity of the foam metal is 80-95%, the average pore size is 0.1-10 mm, and the compressive strength is not less than 250 kPa; Preferably, the foam metal is selected from one or more of foam copper, foam aluminum and foam nickel.

3. The composite material according to claim 1, characterized in that The thermally conductive material is selected from one or more of silicon carbide, graphite, graphene oxide, high thermal conductivity organic silicone grease and high thermal conductivity organic silicone gel; Preferably, the thermally conductive material is a highly thermally conductive silicone gel.

4. The composite material according to claim 1 or 3, characterized in that: The porous material is selected from one or more of activated carbon, molecular sieve, silica gel and MOFs materials; Preferably, the specific surface area of ​​the activated carbon is 400-2000m 2 / g, average pore diameter of 0.5-20nm, pore volume of 0.4-0.9cm 3 / g; Preferably, the specific surface area of ​​the molecular sieve is 50-500m 2 / g, average pore diameter of 1-60nm, pore volume of 0.1-0.4cm 3 / g; Preferably, the specific surface area of ​​the silica gel is 100-6000m 2 / g, average pore diameter of 1.5-50nm, pore volume of 0.1-0.6cm 3 / g. Preferably, the specific surface area of ​​the MOFs material is 800-2500m 2 / g, average pore diameter of 0.5-5nm, pore volume of 0.4-1.1cm 3 / g.

5. A method for preparing a composite material for adsorbing VOCs according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) mixing a thermally conductive material with an organic solvent to obtain a thermally conductive material mixture; (2) mixing the porous material with the thermally conductive material mixture to obtain a slurry mixture; (3) placing the foamed metal in the slurry mixture for ultrasonic vibration, followed by sedimentation to obtain a composite material precursor; (4) air-drying and drying the composite material precursor.

6. The preparation method according to claim 5, characterized in that: In step (1), the organic solvent is selected from one or more of methanol, ethanol, N,N-dimethylformamide, dichloromethane and 1,2-dichloroethane; Preferably, in step (1), the organic solvent is ethanol.

7. The preparation method according to claim 5 or 6, characterized in that: In step (1), the content of the thermally conductive material in the thermally conductive material mixture is 10-80 wt%.

8. The preparation method according to claim 5, characterized in that: In step (2), the content of the porous material in the slurry mixture is 10-80 wt%.

9. The preparation method according to claim 5, 6 or 8, characterized in that: The weight ratio of the amount of the foam metal to the amount of the porous material is 0.15-0.2:1; Preferably, in step (3), the ultrasonic oscillation time is 10-60 min.

10. The preparation method according to claim 5 or 9, characterized in that: In step (3), the sedimentation time is 4-20 hours.

11. Use of the composite material for adsorbing VOCs according to any one of claims 1 to 4 in adsorbing VOCs.

Citation Information

Patent Citations

  • Shaped MOF-based composite phase change material and preparation method and application thereof

    CN110484213A

  • Foam metal supporting adsorption material and preparation method thereof

    CN113117647A

  • Foamed aluminum modified activated carbon fiber and preparation method thereof

    CN113713767A

Cited By

  • Metal organic framework material as well as preparation method and application thereof

    CN119931084A